An insight into SARS-CoV-2 membrane protein interaction with spike, envelope, and nucleocapsid proteins. Issue 3 (11th February 2023) - Kumar, Prateek; Kumar, Amit; Garg, Neha; Giri, Rajanish
Abstract: Intraviral protein–protein interactions are crucial for replication, pathogenicity, and viral assembly. Among these, virus assembly is a critical step as it regulates the arrangements of viral structural proteins and helps in the encapsulation of genomic material. SARS-CoV-2 structural proteins play an essential role in the self-rearrangement, RNA encapsulation, and mature virus particle formation. In SARS-CoV, the membrane protein interacts with the envelope and spike protein in Endoplasmic Reticulum Golgi Intermediate Complex (ERGIC) to form an assembly in the lipid bilayer, followed by membrane-ribonucleoprotein (nucleocapsid) interaction. In this study, we tried to understand the interaction of membrane protein's interaction with envelope, spike, and nucleocapsid proteins using protein–protein docking. Further, simulation studies were performed up to 100 ns to examine the stability of protein–protein complexes of Membrane-Envelope, Membrane-Spike, and Membrane-Nucleocapsid proteins. Prime MM-GBSA showed high binding energy calculations for the simulated structures than the docked complex. The interactions identified in our study will be of great importance, as it provides valuable insight into the protein–protein complex, which could be the potential drug targets for future studies. Communicated by Ramaswamy H. Sarma